Is it possible to have a mathematics club dedicated to teacher education? - Lopes, Anemari Roesler Luersen Vieira (2024)
This article focuses on teacher education and starts from the following question: how can we collectively build a space that allows teachers to overcome the limited vision of pedagogical activity that has tried to establish itself as hegemonic within Brazilian classrooms? In the search for answers, its main objective is to present reflections on the potential of a project, called Mathematics Club, which emerges as a privileged space for the mathematics teachers education. Based on the Cultural-Historical Theory and the results of research developed in this area, the constitution of this space and its formative potential are discussed, listing its historical movement, which began at the University of São Paulo in 1999 and, over time, spread to different regions of Brazil. As a main result, the study indicates that the transposition of the current training model can only be consolidated if teachers in initial and continuing training have the opportunity to experience experiences that lead to the understanding and transformation of the reality that surrounds them. This involves creating spaces that place them as subjects of their activity, enabling them to understand school as a space for the appropriation of culture through theoretical knowledge, such as mathematics, through an intentional organization of teaching that has as its main objective the development of the maximum capacities of students, in a movement of sharing knowledge and experiences.